Efficiency of thermal endometrial ablation in cases of menorrhagia in the opinion of treated patients - Sobkiewicz, Sławomir; Lech, Waldemar (Menopause Review/Przegląd Menopauzalny, 2004)
Objectives: To assess the efficiency of thermal endometrial ablation in the management of menorrhagia based on questionnaires completed by patients. Material and methods: 32 women aged 41–53 who underwent thermal endometrial ablation due to menorrhagia in 1998–2002 were included into the study. All patients had undergone first diagnostic procedures, and then thermal endometrial ablation using the catheter by MEDCOM was done. Observational study based on completed questionnaires assessed the intensity of symptoms before, 3 and 6 months after therapy. Results: The questionnaires completed by 31 patients were returned and analysed. 29 women reported a significant reduction in bleeding after therapy, and in 2 patients bleeding persisted or became more severe. The average length of menstruation as well as the intensity of uterine bleeding decreased significantly after treatment. The average satisfaction from treatment in patients was 7.2±2.5 points after 3 months, and 6.6±2.9 points after 6 months on a ten-point scale. Conclusions: Efficiency of thermal endometrial ablation in the treatment of menorrhagia was well estimated by treated patients. These data and relatively low costs make the method an alternative to hysterectomy in the treatment of menorrhagia, especially in women who would like to keep uterus.